More Than Words: Do Gendered Linguistic Structures Widen the Gender Gap in Entrepreneurial Activity? - Diana M. Hechavarría; Siri A. Terjesen; Pekka Stenholm; Malin Brännback; Stefan Lång (Wiley, 2025)
Leveraging linguistic relativity theory which suggests that language systems structure thought and action, we investigate the relationship between gendered linguistic structures and the persistent gender gap in early-stage entrepreneurial activity. We use country-level data from 105 countries in 2001–2015 with 55 different languages, and incorporate 32 controls covering a broad range of factors previously associated with entrepreneurial activity. We find that in countries where the dominant language's structure incorporates sex-based systems and gender-differentiated pronouns, there is a greater gender gap in entrepreneurial activity. Our results suggest that gendered linguistic structures reinforce gender stereotypes and discourage women's entry into entrepreneurship.